COMMODIFICATION OF RELIGIOUS RITUALS: A PORTRAIT OF THE MEANING OF HAJJ AND UMRAH IN INDONESIA - Sahlul Fuad (UIN Syarif Hidayatullah Jakarta, 2022)
Abstract. This article discusses religious behaviour related to Hajj and Umrah which have become a form of commodification of religion. Hajj and Umrah, as two types of religious rituals in Islam, are extensively interrelated with other existing social institutions. Therefore, they have a more complex association compared to other religious rituals. Hajj and Umrah have not only given birth to various meanings for those who perform the rituals, but also become a tourism industry with a wide and promising market share. Hajj and Umrah seem to be able to change other religious behaviours such as the increase of obedience’s intensity in worshiping God. In addition, Hajj and Umrah in Indonesia are not only packaged and marketed as profitable commodities, but also used as tools for criminal acts. Abstrak. Artikel ini membahas tentang perilaku keagamaan terkait haji dan umrah yang telah menjadi bentuk komodifikasi agama. Haji dan Umrah, sebagai dua jenis ritual keagamaan dalam Islam, sangat erat kaitannya dengan pranata sosial lain yang ada. Oleh karena itu, mereka memiliki asosiasi yang lebih kompleks dibandingkan dengan ritual keagamaan lainnya. Haji dan Umrah tidak hanya melahirkan berbagai makna bagi yang menunaikan ibadah haji, tetapi juga menjadi industri pariwisata dengan pangsa pasar yang luas dan menjanjikan. Haji dan Umrah tampaknya mampu mengubah perilaku keagamaan lainnya seperti peningkatan intensitas ketaatan dalam beribadah kepada Allah. Selain itu, haji dan umrah di Indonesia tidak hanya dikemas dan dipasarkan sebagai komoditas yang menguntungkan, tetapi juga digunakan sebagai alat untuk melakukan tindak pidana.